Application of the real-time PCR Taqman allelic discrimination assay for the detection of Isoniazid and/or Rifampicin resistant Mycobacterium Tuberculosis from clinical samples - Nguyen, Thi Binh Nguyen; Tran, Thi Hong Van; Nguyen, Thi Kieu Diem; Truong, Van Hue; Tran, Tuyet Ngoc; Phan, van Bao Thang; Nguyen, Thi Tuyen; Nguyen, Hoang Bach; Mai, Van Tuan; Paola, Molicotti; Ngo, Viet Quynh Tram (Tạp chí Y Dược Huế, 2023)
Background: Drug-resistant Tuberculosis (DR-TB) is challenging public health problem in countries with high tuberculosis prevalence and limited resources. Developing and applying the most appropriate and effective methods for diagnosing DR-TB from clinical samples is necessary, allowing a more rapid detection method for large-scale screening. Methods: Applying real-time PCR Taqman allelic discrimination with a PCR Taqman probes panel to identifying the DR-TB associated mutations in rpoB and katG of Mycobacterium Tuberculosis from isolates and clinical samples. Results: Comparing results of the real-time PCR allelic and DNA sequencing results, the sensitivity and specificity for Isoniazid resistance detection by analysing katG were found 95%(75.1 - 99.8) and 100%, Rifampicin resistance determining region (RRDR) of rpoB were found 95.5(77.16 - 99.88) and 100%, respectively. The real-time PCR TaqMan allelic discrimination also showed the sensitivities 100% for both katG and rpoB, and the specificities were 93.55% (78.58 - 99.21) for the rpoB and 93.94% (79.77 - 99.26) for the katG from clinical samples. Conclusions: This study showed that the real-time PCR taqman allelic discrimination assay is useful for detection of TB and DR-TB because of an accurate and rapid diagnosis in the early stages.